(untitled) (Journal of Preventive and Social Medicine, 2023)
Background: Research experience in medical education is strongly related to post graduate course curriculum and is also highly associated with future career achievements but conducting research is a difficult task at student level. Many hurdles are faced by post-graduate medical students during conducting biomedical research in Bangladesh. Previously doctors were either clinicians or researchers but now it is realized that a good clinician is a good researcher and able to be a competent physician & scientist. This study was conducted to find out practice on biomedical research and barriers experienced by the post-graduate medical students during conducting it in Bangladesh. Methods: This cross-sectional type of descriptive study was carried out in the different medical colleges and Universities all over the Bangladesh over a period of 12 months from January to December 2020 among the postgraduate students of different medical colleges. Approval from the Ethical Review Committee (ERC) of Rajshahi Medical College was obtained prior to the commencement of the study and convenient sampling technique was used. Pre-designed, validated, structured questionnaire was used to collect data from 325 respondents on practice of biomedical research and 5-point Likert scale was used for assessment of barriers to its practice. Results: Regarding practice on research, 35.10% respondents had satisfactory practice on biomedical research and only 13.20% had published their research report in journals. Lack of research training & necessary skills (73.80%), lack of fund (68.80%), lack of interest & motivation (66.20%) and lack of appropriate knowledge (65.50%) were commonly faced barrier by the post-graduate medical students. Students who were in Ph. D (100%) and MPH course (68.20%) had more practice on biomedical research than those who were in MD/MS (35.80%), M. Phil (32.40%), FCPS (39.20%) and Diploma (4.90%) courses (p < 0.05). Thesis part (39.50%) and dissertation part (39.20%) post-graduate students had also more practice on biomedical research than those who were in Diploma (4.90%) courses (p < 0.05). But relationship of practice on biomedical research of the respondents was not statistically significant with age, gender, religion, type of medical college of MBBS passing, marital status, parental and spouse educational status (p > 0.05). Conclusion: The study revealed that the post-graduate medical students faced various types of difficulties during conducting research. So, respective higher authorities must be careful to solve their problems during conducting biomedical research. JOPSOM 2021; 41(1):25-34